Insulating wear-resistant composite coating and preparation method thereof
By preparing an insulating wear-resistant composite coating on the bearing surface, the problem of poor coating performance is solved, the insulation, breakdown resistance and wear resistance are improved, the service life of the bearing is extended and the operation safety of the motor equipment is enhanced.
Patent Information
- Application Number
- CN202411770335.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-04
AI Technical Summary
The coating performance of existing bearing components is poor, resulting in electrocorrosion, temperature increases, vibration increases, shortening service life and affecting the operating safety of motor equipment.
The coating is prepared on the bearing surface by mechanical mixing and plasma spraying technology using an insulating wear-resistant composite coating, including a metal cermet transition layer, a single ceramic layer and a composite ceramic surface layer.
It improves the insulation, breakdown resistance, combination performance and wear resistance of the coating, extends the service life of the bearing, and enhances the operating safety of the motor equipment.
Smart Images

Figure CN119243070B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of material surface treatment, and in particular to an insulating wear-resistant composite coating and a method for preparing the insulating wear-resistant composite coating. Background Art
[0002] In recent years, new energy vehicles, high-speed rail, electric power, mechanical metallurgy and other fields have developed rapidly. In order to ensure the performance and life of components in various fields, material coatings have played a vital role, which has also made the quality of coatings a focus of attention.
[0003] Currently, there is a problem of poor coating performance for components such as bearings.
[0004] It should be noted that the information disclosed in the above background technology section is only used to enhance the understanding of the background of the present disclosure, and therefore may include information that does not constitute the prior art known to ordinary technicians in the field. Summary of the invention
[0005] The purpose of the present disclosure is to provide an insulating wear-resistant composite coating and a method for preparing the insulating wear-resistant composite coating, thereby overcoming the problem of poor coating performance at least to a certain extent.
[0006] According to the first aspect of the present disclosure, an insulating wear-resistant composite coating is provided, which includes a metal-ceramic transition layer, a single ceramic layer and a multiphase ceramic surface layer; the metal-ceramic transition layer contains a metal phase and a ceramic phase, the metal phase is a combination of one or more of nickel, aluminum, cobalt, chromium, and yttrium, and the ceramic phase is a combination of one or more of aluminum oxide, yttrium oxide, zirconium oxide, titanium oxide, and chromium oxide; the single ceramic layer is aluminum oxide; the multiphase ceramic surface layer contains a main phase and a doped phase, the main phase is aluminum oxide, and the doped phase is a combination of one or more of yttrium oxide, zirconium oxide, titanium oxide, and chromium oxide.
[0007] Optionally, the mass percentage of the ceramic phase in the metal-ceramic transition layer is 5% to 50%.
[0008] Optionally, the mass percentage of the doped phase in the composite ceramic surface layer is 1% to 30%.
[0009] Optionally, the thickness of the metal ceramic transition layer is 30μm to 100μm, and the porosity is less than or equal to 5%; the thickness of the single ceramic layer is 100μm to 300μm, and the porosity is less than or equal to 5%; the thickness of the composite ceramic surface layer is 100μm to 400μm, and the porosity is less than or equal to 3%.
[0010] Optionally, the DC breakdown voltage of the insulating wear-resistant composite coating is greater than or equal to 4 kV, the bonding strength is greater than or equal to 25 MPa, and the hardness is 1000 HV 0.3 Up to 1400HV0.3 The average friction coefficient is 0.5 to 0.8, and the wear rate is 1.5×10 -6 mm·N -1 ·m -1 Up to 3.0×10 -6 mm·N -1 ·m -1 .
[0011] According to the second aspect of the present disclosure, a method for preparing an insulating wear-resistant composite coating is provided, and the insulating wear-resistant composite coating is any one of the above-mentioned insulating wear-resistant composite coatings, wherein the method for preparing the insulating wear-resistant composite coating comprises: mechanically mixing metal powder corresponding to the metal and ceramic powder corresponding to the ceramic, and obtaining metal-ceramic transition layer powder after drying; mechanically mixing alumina powder and doping corresponding powder, and obtaining complex ceramic surface layer powder after drying; using the metal-ceramic transition layer powder and adopting plasma spraying to prepare a metal-ceramic transition layer on the surface of the substrate; using alumina powder and adopting plasma spraying to prepare a single ceramic layer on the metal-ceramic transition layer; using complex ceramic surface layer powder and adopting plasma spraying to prepare a complex ceramic surface layer on the single ceramic layer.
[0012] Optionally, the method for preparing the insulating wear-resistant composite coating further includes: before preparing the metal-ceramic transition layer, cleaning and drying the substrate; and roughening the cleaned and dried substrate using a sandblasting machine.
[0013] Optionally, process parameters for roughening the substrate using a sandblasting machine include: a sandblasting pressure of 0.2 MPa to 0.6 MPa, a distance between the sandblasting gun and the substrate of 5 cm to 20 cm, and a sandblasting angle of 60° to 90°.
[0014] Optionally, the process parameters for preparing the metal ceramic transition layer include: spraying power of 40kW to 80kW, main gas flow of 60L / min to 200L / min, powder feeding rate of 10g / min to 30g / min, and spraying distance of 8cm to 15cm.
[0015] Optionally, the process parameters for preparing a single ceramic layer and / or a composite ceramic surface layer include: spraying power of 40 kW to 100 kW, main gas flow of 60 L / min to 200 L / min, powder feeding rate of 10 g / min to 30 g / min, and spraying distance of 8 cm to 15 cm.
[0016] Optionally, the substrate is bearing steel, stainless steel, or an alloy.
[0017] Through the scheme of the exemplary embodiment of the present disclosure, on the one hand, the metal ceramic transition layer of the present disclosure contains a ceramic phase, thereby improving the insulation of the layer, reducing the internal dielectric loss, and improving the anti-puncture ability of the coating. While ensuring the insulation performance of the coating, the metal ceramic transition layer can improve the deposition efficiency and density of the external coating, and improve the coating bonding performance. On the other hand, the present disclosure constructs a double-layer structure of a single ceramic layer and a multi-phase ceramic surface layer, thereby achieving insulation and wear-resistant protection. The single alumina ceramic layer has a uniform and dense structure and can form a dense insulating barrier for the substrate. The multi-phase ceramic surface layer, as a functional layer, can play a synergistic strengthening role in regulating the wear resistance and insulation performance of the coating, giving full play to the combination effect between layers. On the other hand, the configuration of the multi-phase ceramic surface layer can be dispersed in layers inside the coating, which can effectively extend the current transmission path and improve the voltage resistance performance of the coating. At the same time, the doped phase in the composite ceramic surface layer will undergo plastic deformation under the action of external loads, causing crack tip passivation and crack cross-linking, avoiding stress concentration at the crack tip, effectively improving the fracture toughness and wear resistance of the coating, and greatly reducing the stress damage of the substrate during transportation, installation and service. On the other hand, the disclosed solution is easy to implement, the coating preparation process is safe and controllable, the coating has high quality, stable performance, and no pollution to the environment. It can be applied in various fields and scenarios and has great application value.
[0018] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The accompanying drawings herein are incorporated into the specification and constitute a part of the specification, illustrate embodiments consistent with the present disclosure, and together with the specification are used to explain the principles of the present disclosure. Obviously, the accompanying drawings described below are only some embodiments of the present disclosure, and for ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without creative work.
[0020] Figure 1 A schematic diagram of an insulating wear-resistant composite coating according to an embodiment of the present disclosure is schematically shown.
[0021] Figure 2 The flowchart of the method for preparing the insulating wear-resistant composite coating according to the embodiment of the present disclosure is schematically shown.
[0022] Figure 3 The macroscopic morphology of the insulating wear-resistant composite coating of Example 1 of the present disclosure is schematically shown.
[0023] Figure 4 Schematically shows Figure 3 Microscopic morphology of area A in the middle.
[0024] Figure 5 The variation curve of the friction coefficient of the insulating wear-resistant composite coating of Example 1 of the present disclosure is schematically shown. DETAILED DESCRIPTION
[0025] Example embodiments will now be described more fully with reference to the accompanying drawings. However, example embodiments can be implemented in a variety of forms and should not be construed as being limited to the examples set forth herein; on the contrary, these embodiments are provided so that the present disclosure will be more comprehensive and complete, and the concepts of the example embodiments are fully conveyed to those skilled in the art. The described features, structures, or characteristics may be combined in any suitable manner in one or more embodiments. In the following description, many specific details are provided to provide a full understanding of the embodiments of the present disclosure. However, those skilled in the art will appreciate that the technical solutions of the present disclosure may be practiced while omitting one or more of the specific details, or other methods, processes, steps, etc. may be adopted. In other cases, known technical solutions are not shown or described in detail to avoid obscuring various aspects of the present disclosure.
[0026] In addition, the accompanying drawings are only schematic illustrations of the present disclosure and are not necessarily drawn to scale. The same reference numerals in the figures represent the same or similar parts, and thus their repeated descriptions will be omitted. The flowcharts shown in the accompanying drawings are only exemplary illustrations and do not necessarily include all the steps. For example, some steps can also be decomposed, while some steps can be combined or partially combined, so the actual execution order may change according to the actual situation.
[0027] With the rapid development of new energy vehicles, high-speed rail, electric power, mechanical metallurgy and other fields, electric drive system technology has been continuously breaking through, bringing severe challenges to the service life of existing components. As the core component of the drive system, the condition of the traction motor bearing directly affects the safe operation of the vehicle. For motor bearings, due to excessive voltage or current leakage, the bearings will suffer from electrocorrosion, resulting in damage to the local structure of the bearing or the lubricating oil film. If the bearing continues to run, its temperature will rise and the vibration will increase, which will seriously shorten the service life of the bearing and the operating safety of the motor equipment. Therefore, it is very necessary to take certain protective measures on the bearing surface to reduce the harm of electrocorrosion damage.
[0028] Preparing an insulating coating on the surface of the inner and outer rings of the bearing is a method of electrical corrosion protection. There are two types of insulating protective coatings, one is an organic resin coating and the other is a ceramic coating. The thermal conductivity of the resin material is low, which results in a large amount of heat generated when the bearing is working and cannot be dissipated in time, reducing the dimensional stability of the material during service. In addition, the organic resin coating is prone to damage during the installation and transportation of the bearing, so the material is not suitable for high temperature, repeated disassembly and assembly, and occasions with high dimensional accuracy requirements. Compared with resin coatings, ceramic coatings show greater advantages in bonding strength, dimensional stability, high and low temperature environment tolerance and insulation performance. However, the bearing will wear against the bearing seat during operation, and it is easily affected by external loads during transportation and installation, causing cracks in the ceramic coating, which reduces the insulation performance and mechanical stability of the ceramic coating.
[0029] High-performance insulating coatings need to have good insulation, bonding performance, fracture toughness and wear resistance. Although some technologies have proposed some coating solutions, these solutions still have problems such as coating peeling, wear and environmental changes that cause the insulation of the coating to decrease.
[0030] In view of this, the present invention discloses a new insulating wear-resistant composite coating and a preparation method thereof, so that the comprehensive performance of the coating including breakdown voltage, bonding strength, wear resistance, etc. can be improved.
[0031] refer to Figure 1 The insulating wear-resistant composite coating of the embodiment of the present disclosure may include a metal-ceramic transition layer, a single ceramic layer and a multi-phase ceramic surface layer. Relative to the substrate, the insulating wear-resistant composite coating is arranged in the order of a metal-ceramic transition layer, a single ceramic layer and a multi-phase ceramic surface layer from the inside to the outside. Among them, the substrate described in the embodiment of the present disclosure may be bearing steel, stainless steel, various alloys, etc., and the present disclosure does not limit this.
[0032] In one aspect, the metal-ceramic transition layer can include a metal phase and a ceramic phase.
[0033] The metal phase can be a combination of one or more of nickel, aluminum, cobalt, chromium, and yttrium. In the case of a combination of multiple metals, an adhesion structure or a coating structure can be formed. Among them, the adhesion structure refers to a powder formed by mixing these types of metals, such as nickel-chromium powder, nickel-chromium-aluminum powder, nickel-cobalt-chromium-aluminum-yttrium powder, etc. The coating structure refers to a powder form formed by one or more metals coating another or more other metals, such as nickel-coated aluminum powder, aluminum-coated nickel-chromium powder, etc.
[0034] The ceramic phase is a combination of one or more of aluminum oxide, yttrium oxide, zirconium oxide, titanium oxide, and chromium oxide.
[0035] In the metal-ceramic transition layer, the mass percentage of the ceramic phase is 5% to 50%, and the rest is the metal phase. In addition, the thickness of the metal-ceramic transition layer is 30 μm to 100 μm, and the porosity is less than or equal to 5%.
[0036] On the other hand, the single ceramic layer of the embodiment of the present disclosure is aluminum oxide, has a thickness of 100 μm to 300 μm, and a porosity of less than or equal to 5%.
[0037] In another aspect, the composite ceramic surface layer comprises a main phase and a doped phase. The main phase may be aluminum oxide. The doped phase may be a combination of one or more of yttrium oxide, zirconium oxide, titanium oxide, and chromium oxide.
[0038] In the composite ceramic surface layer, the mass percentage of the doped phase is 1% to 30%. In addition, the thickness of the composite ceramic surface layer is 100 μm to 400 μm, and the porosity is less than or equal to 3%.
[0039] The insulating wear-resistant composite coating of the embodiment of the present disclosure has a DC breakdown voltage greater than or equal to 4 kV, a bonding strength greater than or equal to 25 MPa, and a hardness of 1000 HV 0.3 Up to 1400HV 0.3 The average friction coefficient is 0.5 to 0.8, and the wear rate is 1.5×10 - 6 mm·N -1 ·m -1 Up to 3.0×10 -6 mm·N -1 ·m -1 .
[0040] Reference below Figure 2 The preparation method of the insulating wear-resistant composite coating according to the embodiment of the present disclosure is described. The insulating wear-resistant composite coating targeted by the preparation method is the insulating wear-resistant composite coating described above. Figure 2 The method for preparing the insulating wear-resistant composite coating according to the embodiment of the present disclosure may include the following steps:
[0041] S20. Mechanically mixing the metal powder corresponding to the metal and the ceramic powder corresponding to the ceramic, and obtaining the metal-ceramic transition layer powder after drying.
[0042] In an exemplary embodiment of the present disclosure, the metal powder corresponding to the metal is a combination of one or more of nickel, aluminum, cobalt, chromium, and yttrium, and the ceramic powder corresponding to the ceramic is a combination of one or more of aluminum oxide, yttrium oxide, zirconium oxide, titanium oxide, and chromium oxide. In other words, the combination of one or more of nickel, aluminum, cobalt, chromium, and yttrium can be mechanically mixed with the combination of one or more of aluminum oxide, yttrium oxide, zirconium oxide, titanium oxide, and chromium oxide. Specifically, the mechanical mixing process can be performed using a ball mill.
[0043] After being evenly mixed, the powder can be placed in an oven for drying to obtain a metal ceramic transition layer powder.
[0044] S22. Mechanically mix the alumina powder and the corresponding doped powder, and obtain the composite ceramic surface layer powder after drying.
[0045] In an exemplary embodiment of the present disclosure, the doped corresponding powder is a combination of one or more of yttrium oxide, zirconium oxide, titanium oxide, and chromium oxide. That is, aluminum oxide can be mechanically mixed with a combination of one or more of yttrium oxide, zirconium oxide, titanium oxide, and chromium oxide. Specifically, a ball mill can be used to perform the mechanical mixing process.
[0046] After being evenly mixed, the powder can be placed in an oven for drying to obtain a composite ceramic surface layer powder.
[0047] It should be noted that the present disclosure does not limit the order of implementing step S20 and step S22. That is, the composite ceramic surface layer powder can be obtained first and then the metal ceramic transition layer powder can be obtained, or the metal ceramic transition layer powder and the composite ceramic surface layer powder can be prepared at the same time.
[0048] In an exemplary embodiment of the present disclosure, the particle size of the metal powder ranges from 25 μm to 75 μm, and the particle size of the ceramic powder ranges from 15 μm to 55 μm.
[0049] S24. A metal-ceramic transition layer is prepared on the surface of a substrate using metal-ceramic transition layer powder and plasma spraying.
[0050] Before preparing the metal-ceramic transition layer, the substrate may be pretreated.
[0051] First, the substrate can be cleaned and dried. For example, the substrate can be placed in an ultrasonic cleaning machine and ultrasonically cleaned with acetone or anhydrous ethanol, and the cleaned substrate is placed in an oven for drying.
[0052] Next, the cleaned and dried substrate can be roughened using a sandblasting machine. The process parameters of this process include: a sandblasting pressure of 0.2 MPa to 0.6 MPa, a distance between the sandblasting gun and the substrate of 5 cm to 20 cm, and a sandblasting angle of 60° to 90°.
[0053] For the process of preparing the metal ceramic transition layer on the substrate surface, the process parameters include: spraying power of 40 kW to 80 kW, main gas flow of 60 L / min to 200 L / min, powder feeding rate of 10 g / min to 30 g / min, and spraying distance of 8 cm to 15 cm. The main gas is, for example, argon gas, which is not limited in the present disclosure.
[0054] S26. A single ceramic layer is prepared on a metal-ceramic transition layer using alumina powder and plasma spraying.
[0055] S28. A composite ceramic surface layer is prepared on a single ceramic layer using composite ceramic surface layer powder and plasma spraying.
[0056] For the process of preparing a single ceramic layer and / or a multiphase ceramic surface layer, the process parameters include: a spraying power of 40 kW to 100 kW, a main gas flow rate of 60 L / min to 200 L / min, a powder feeding rate of 10 g / min to 30 g / min, and a spraying distance of 8 cm to 15 cm. The main gas is, for example, argon gas, which is not limited in the present disclosure.
[0057] Through the insulating wear-resistant composite coating scheme of the above-mentioned embodiment of the present disclosure, on the one hand, the metal ceramic transition layer of the present disclosure contains a ceramic phase, thereby improving the insulation of the layer, reducing the internal dielectric loss, and improving the anti-puncture ability of the coating. While ensuring the insulation performance of the coating, the metal ceramic transition layer can improve the deposition efficiency and density of the external coating and improve the coating bonding performance. On the other hand, the present disclosure constructs a double-layer structure of a single ceramic layer and a multi-phase ceramic surface layer, thereby achieving insulating wear-resistant protection. The single alumina ceramic layer has a uniform and dense structure and can form a dense insulating barrier for the substrate. The multi-phase ceramic surface layer, as a functional layer, can play a synergistic strengthening role in regulating the wear resistance and insulation performance of the coating, giving full play to the combination effect between layers. On the other hand, the outer layer configuration of the multi-phase ceramic surface layer can be dispersed in layers inside the coating, which can effectively extend the current transmission path and improve the voltage resistance performance of the coating. At the same time, the composite ceramic surface layer will undergo plastic deformation under the action of external loads, causing crack tip passivation and crack cross-linking, avoiding stress concentration at the crack tip, effectively improving the fracture toughness and wear resistance of the coating, and greatly reducing stress damage to the bearing matrix during transportation, installation and service. On the other hand, the disclosed solution is easy to implement, the coating preparation process is safe and controllable, the coating quality is high, the performance is stable, and it is pollution-free to the environment. It can be applied to various fields and scenarios, especially suitable for aerospace, rail transportation, shipbuilding and ocean, weapons industry and construction industries that require electrical insulation protection and frequent disassembly and assembly, and has great application value.
[0058] The scheme of the embodiment of the present disclosure is described below through examples and comparative examples.
[0059] Example 1
[0060] The insulating wear-resistant composite coating includes a metal-ceramic transition layer, a single ceramic layer and a multi-phase ceramic surface layer. In the metal-ceramic transition layer, the metal phase is nickel-chromium, with a mass percentage of 90%; the ceramic phase is aluminum oxide, with a mass percentage of 10%. The single ceramic layer is an aluminum oxide coating. In the multi-phase ceramic surface layer, the main phase is aluminum oxide, the doped phase is yttrium oxide, and the mass percentage of the doped phase is 10%.
[0061] The coating preparation method corresponding to this embodiment may include:
[0062] First, the bearing steel substrate is placed in an ultrasonic cleaning machine, ultrasonically cleaned with acetone or anhydrous ethanol, and then dried in an oven. A sandblaster is used to roughen the cleaned and dried substrate. The sandblasting pressure is 0.3 MPa, the distance between the sandblasting gun and the substrate is 10 cm, and the sandblasting angle is 90°.
[0063] At the same time, powder preparation can be performed. Specifically, on the one hand, nickel-chromium powder with a particle size of 25 μm to 45 μm and alumina ceramic powder with a particle size of 15 μm to 45 μm are placed in a ball mill for mechanical mixing, and after mixing evenly, they are placed in an oven for drying to obtain metal ceramic transition layer powder. On the other hand, alumina powder with a particle size of 15 μm to 45 μm and yttrium oxide powder with a particle size of 15 μm to 30 μm are placed in a ball mill for mechanical mixing, and after mixing evenly, they are placed in an oven for drying to obtain a composite ceramic surface layer powder.
[0064] Next, plasma spraying technology was used to prepare a metal-ceramic transition layer on the roughened bearing steel surface. The process parameters included: spraying power of 40kW, main gas flow of 60L / min, powder feeding rate of 15g / min, and spraying distance of 10cm. The thickness of the prepared metal-ceramic transition layer was 50μm and the porosity was 4.5%.
[0065] Then, plasma spraying technology is used to spray a single ceramic layer and a composite ceramic surface layer on the metal ceramic transition layer in sequence. The process parameters for preparing a single ceramic layer include: spraying power of 50kW, main gas flow rate of 80L / min, powder feeding rate of 20g / min, and spraying distance of 10cm. The thickness of the prepared single ceramic layer is 200μm and the porosity is 3.3%. The process parameters for preparing a composite ceramic surface layer include: spraying power of 50kW, main gas flow rate of 100L / min, powder feeding rate of 25g / min, and spraying distance of 10cm. The thickness of the prepared composite ceramic surface layer is 200μm and the porosity is 2.8%.
[0066] Figure 3 The macroscopic morphology of the insulating wear-resistant composite coating of Example 1 of the present disclosure is schematically shown. Figure 3The resin on the composite ceramic surface layer is used for subsequent sample mounting. Figure 3 It can be seen that the insulating wear-resistant composite coating prepared in the embodiment of the present disclosure has good density, no voids and no cracks.
[0067] Figure 4 Schematically shows Figure 3 Microscopic morphology of area A in the middle. Figure 4 The composite ceramic surface layer prepared by the disclosed solution has good density and no cracks.
[0068] Figure 5 The variation curve of the friction coefficient of the insulating wear-resistant composite coating of Example 1 of the present disclosure is schematically shown. Figure 5 It can be seen that the friction coefficient of the insulating wear-resistant composite coating using the solution of Example 1 of the present disclosure is 0.72.
[0069] Example 2
[0070] The insulating wear-resistant composite coating includes a metal-ceramic transition layer, a single ceramic layer and a multi-phase ceramic surface layer. In the metal-ceramic transition layer, the metal phase is nickel-clad aluminum with a mass percentage of 95%; the ceramic phase is zirconium oxide with a mass percentage of 5%. The single ceramic layer is an aluminum oxide coating. In the multi-phase ceramic surface layer, the main phase is aluminum oxide, the doped phase is zirconium oxide, and the mass percentage of the doped phase is 15%.
[0071] The coating preparation method corresponding to this embodiment may include:
[0072] First, the bearing steel substrate is placed in an ultrasonic cleaning machine, ultrasonically cleaned with acetone or anhydrous ethanol, and then dried in an oven. A sandblaster is used to roughen the cleaned and dried substrate. The sandblasting pressure is 0.4 MPa, the distance between the sandblasting gun and the substrate is 15 cm, and the sandblasting angle is 85°.
[0073] At the same time, powder preparation can be performed. Specifically, on the one hand, nickel-clad aluminum with a particle size of 25 μm to 45 μm and zirconium oxide ceramic powder with a particle size of 25 μm to 45 μm are placed in a ball mill for mechanical mixing, and after mixing evenly, they are placed in an oven for drying to obtain a metal ceramic transition layer powder. On the other hand, aluminum oxide powder with a particle size of 15 μm to 45 μm and zirconium oxide powder with a particle size of 15 μm to 35 μm are placed in a ball mill for mechanical mixing, and after mixing evenly, they are placed in an oven for drying to obtain a composite ceramic surface layer powder.
[0074] Next, plasma spraying technology was used to prepare a metal-ceramic transition layer on the roughened bearing steel surface. The process parameters included: spraying power of 70kW, main gas flow of 150L / min, powder feeding rate of 30g / min, and spraying distance of 15cm. The thickness of the prepared metal-ceramic transition layer was 80μm and the porosity was 4%.
[0075] Then, plasma spraying technology is used to spray a single ceramic layer and a composite ceramic surface layer on the metal ceramic transition layer in sequence. The process parameters for preparing a single ceramic layer include: spraying power of 60kW, main gas flow rate of 150L / min, powder feeding rate of 30g / min, and spraying distance of 12cm. The thickness of the prepared single ceramic layer is 260μm and the porosity is 2.7%. The process parameters for preparing a composite ceramic surface layer include: spraying power of 70kW, main gas flow rate of 120L / min, powder feeding rate of 20g / min, and spraying distance of 12cm. The thickness of the prepared composite ceramic surface layer is 300μm and the porosity is 2%.
[0076] Example 3
[0077] The insulating wear-resistant composite coating includes a metal-ceramic transition layer, a single ceramic layer and a multi-phase ceramic surface layer. In the metal-ceramic transition layer, the metal phase is nickel-chromium-aluminum, with a mass percentage of 80%; the ceramic phase is aluminum oxide and titanium oxide, both of which have a mass percentage of 10%. The single ceramic layer is an aluminum oxide coating. In the multi-phase ceramic surface layer, the main phase is aluminum oxide, and the doped phases are zirconium oxide and titanium oxide, and the mass percentages of the two doped phases are both 5%.
[0078] The coating preparation method corresponding to this embodiment may include:
[0079] First, the bearing steel substrate is placed in an ultrasonic cleaning machine, ultrasonically cleaned with acetone or anhydrous ethanol, and then dried in an oven. A sandblaster is used to roughen the cleaned and dried substrate. The sandblasting pressure is 0.5 MPa, the distance between the sandblasting gun and the substrate is 12 cm, and the sandblasting angle is 90°.
[0080] At the same time, powder preparation can be performed. Specifically, on the one hand, nickel-chromium-aluminum with a particle size of 45 μm to 75 μm and aluminum oxide and titanium oxide ceramic powder with a particle size of 15 μm to 55 μm are placed in a ball mill for mechanical mixing, and after mixing evenly, they are placed in an oven for drying to obtain a metal ceramic transition layer powder. On the other hand, aluminum oxide powder with a particle size of 15 μm to 55 μm and zirconium oxide and titanium oxide powder with a particle size of 15 μm to 55 μm are placed in a ball mill for mechanical mixing, and after mixing evenly, they are placed in an oven for drying to obtain a composite ceramic surface layer powder.
[0081] Next, plasma spraying technology was used to prepare a metal-ceramic transition layer on the roughened bearing steel surface. The process parameters included: spraying power of 50kW, main gas flow of 100L / min, powder feeding rate of 10g / min, and spraying distance of 8cm. The thickness of the prepared metal-ceramic transition layer was 60μm and the porosity was 3.1%.
[0082] Then, plasma spraying technology is used to spray a single ceramic layer and a composite ceramic surface layer on the metal ceramic transition layer in sequence. The process parameters for preparing a single ceramic layer include: spraying power of 40kW, main gas flow of 60L / min, powder feeding rate of 25g / min, and spraying distance of 15cm. The thickness of the prepared single ceramic layer is 200μm and the porosity is 5.0%. The process parameters for preparing a composite ceramic surface layer include: spraying power of 80kW, main gas flow of 200L / min, powder feeding rate of 30g / min, and spraying distance of 15cm. The thickness of the prepared composite ceramic surface layer is 400μm and the porosity is 2.2%.
[0083] Example 4
[0084] The insulating wear-resistant composite coating includes a metal-ceramic transition layer, a single ceramic layer and a multi-phase ceramic surface layer. In the metal-ceramic transition layer, the metal phase is nickel-cobalt-chromium-aluminum-yttrium, with a mass percentage of 50%; the ceramic phase is zirconium oxide and yttrium oxide, both of which have a mass percentage of 25%. The single ceramic layer is an aluminum oxide coating. In the multi-phase ceramic surface layer, the main phase is aluminum oxide, the doped phase is yttrium oxide, and the mass percentage of the doped phase is 10%.
[0085] The coating preparation method corresponding to this embodiment may include:
[0086] First, the bearing steel substrate is placed in an ultrasonic cleaning machine, ultrasonically cleaned with acetone or anhydrous ethanol, and then dried in an oven. A sandblaster is used to roughen the cleaned and dried substrate. The sandblasting pressure is 0.6 MPa, the distance between the sandblasting gun and the substrate is 20 cm, and the sandblasting angle is 60°.
[0087] At the same time, powder preparation can be performed. Specifically, on the one hand, the nickel-cobalt-chromium-aluminum-yttrium with a particle size of 25 μm to 75 μm and the zirconium oxide and yttrium oxide ceramic powder with a particle size of 25 μm to 45 μm are placed in a ball mill for mechanical mixing, and after mixing evenly, they are placed in an oven for drying to obtain a metal ceramic transition layer powder. On the other hand, the aluminum oxide powder with a particle size of 25 μm to 45 μm and the yttrium oxide powder with a particle size of 15 μm to 45 μm are placed in a ball mill for mechanical mixing, and after mixing evenly, they are placed in an oven for drying to obtain a composite ceramic surface layer powder.
[0088] Next, plasma spraying technology was used to prepare a metal-ceramic transition layer on the roughened bearing steel surface. The process parameters included: spraying power of 80kW, main gas flow of 200L / min, powder feeding rate of 25g / min, and spraying distance of 10cm. The thickness of the prepared metal-ceramic transition layer was 100μm and the porosity was 5.0%.
[0089] Then, plasma spraying technology is used to spray a single ceramic layer and a composite ceramic surface layer on the metal ceramic transition layer in sequence. The process parameters for preparing a single ceramic layer include: spraying power of 80kW, main gas flow of 110L / min, powder feeding rate of 10g / min, and spraying distance of 15cm. The thickness of the prepared single ceramic layer is 100μm and the porosity is 3.1%. The process parameters for preparing a composite ceramic surface layer include: spraying power of 100kW, main gas flow of 60L / min, powder feeding rate of 30g / min, and spraying distance of 15cm. The thickness of the prepared composite ceramic surface layer is 350μm and the porosity is 3%.
[0090] Example 5
[0091] The insulating wear-resistant composite coating includes a metal-ceramic transition layer, a single ceramic layer and a multi-phase ceramic surface layer. In the metal-ceramic transition layer, the metal phase is nickel-chromium-aluminum-yttrium, with a mass percentage of 90%; the ceramic phase is aluminum oxide and titanium oxide, both of which have a mass percentage of 5%. The single ceramic layer is an aluminum oxide coating. In the multi-phase ceramic surface layer, the main phase is aluminum oxide, and the doped phases are titanium oxide and yttrium oxide, and the mass percentage of the two doped phases is 30%.
[0092] The coating preparation method corresponding to this embodiment may include:
[0093] First, the bearing steel substrate is placed in an ultrasonic cleaning machine, ultrasonically cleaned with acetone or anhydrous ethanol, and then dried in an oven. A sandblaster is used to roughen the cleaned and dried substrate. The sandblasting pressure is 0.2 MPa, the distance between the sandblasting gun and the substrate is 5 cm, and the sandblasting angle is 80°.
[0094] At the same time, powder preparation can be performed. Specifically, on the one hand, nickel-chromium-aluminum-yttrium with a particle size of 45 μm to 75 μm and aluminum oxide and titanium oxide ceramic powder with a particle size of 15 μm to 55 μm are placed in a ball mill for mechanical mixing, and after mixing evenly, they are placed in an oven for drying to obtain a metal ceramic transition layer powder. On the other hand, aluminum oxide powder with a particle size of 15 μm to 55 μm and titanium oxide and yttrium oxide powder with a particle size of 15 μm to 30 μm are placed in a ball mill for mechanical mixing, and after mixing evenly, they are placed in an oven for drying to obtain a composite ceramic surface layer powder.
[0095] Next, plasma spraying technology was used to prepare a metal-ceramic transition layer on the roughened bearing steel surface. The process parameters included: spraying power of 60kW, main gas flow of 130L / min, powder feeding rate of 15g / min, and spraying distance of 12cm. The thickness of the prepared metal-ceramic transition layer was 30μm and the porosity was 3.9%.
[0096] Then, plasma spraying technology is used to spray a single ceramic layer and a composite ceramic surface layer on the metal ceramic transition layer in sequence. The process parameters for preparing a single ceramic layer include: spraying power of 100kW, main gas flow of 200L / min, powder feeding rate of 20g / min, and spraying distance of 8cm. The thickness of the prepared single ceramic layer is 300μm and the porosity is 3.4%. The process parameters for preparing a composite ceramic surface layer include: spraying power of 40kW, main gas flow of 150L / min, powder feeding rate of 10g / min, and spraying distance of 8cm. The thickness of the prepared composite ceramic surface layer is 100μm and the porosity is 2.4%.
[0097] Comparative Example 1
[0098] The composite coating is composed of a metal-ceramic transition layer and a single ceramic layer. The thickness of the single ceramic layer is 400 μm. The rest of the process is the same as in Example 1.
[0099] Comparative Example 2
[0100] The composite coating consists of a metal-ceramic transition layer, a single ceramic layer and a polymer organic coating. The thickness of the single ceramic layer is 300μm. The preparation process of the polymer organic coating includes: spraying the polymer organic coating on the surface of the ceramic layer with a spray gun, then placing it in an oven at 25℃ to 120℃ to drain the solvent, repeating 3 to 4 times until the thickness of the organic coating is 100μm, and finally heating the sample to 70℃ to 200℃ in an oven for curing, and cooling to room temperature.
[0101] In the above embodiment, the purity of acetone and anhydrous ethanol is analytically pure, the purity of the metal powder and the purity of the ceramic powder are both greater than or equal to 99.9%, and the volume purity of argon is greater than or equal to 99.99%.
[0102] The DC breakdown voltage, bonding strength, hardness, friction coefficient and wear rate of the coatings of the above embodiments and comparative examples were tested. The test results are shown in Table 1:
[0103] Table 1
[0104]
[0105] It can be seen from Table 1 that, compared with Examples 1 to 5, the hardness and wear resistance of Comparative Example 1 are not good, and the bonding strength, hardness and wear resistance of Comparative Example 2 are seriously deteriorated. In other words, the scheme of the embodiment of the present disclosure can improve the comprehensive performance of the coating, and the coating performance can be controlled by adjusting the process parameters.
[0106] It should be noted that although the steps of the method in the present disclosure are described in a specific order in the drawings, this does not require or imply that the steps must be performed in this specific order, or that all the steps shown must be performed to achieve the desired results. Additionally or alternatively, some steps may be omitted, multiple steps may be combined into one step, and / or one step may be decomposed into multiple steps, etc.
[0107] In addition, the above-mentioned figures are only schematic illustrations of the processes included in the method according to the exemplary embodiments of the present disclosure, and are not intended to be limiting. It is easy to understand that the processes shown in the above-mentioned figures do not indicate or limit the time sequence of these processes. In addition, it is also easy to understand that these processes can be performed synchronously or asynchronously, for example, in multiple modules.
[0108] Those skilled in the art will readily appreciate other embodiments of the present disclosure after considering the specification and practicing what is disclosed herein. This application is intended to cover any variations, uses, or adaptations of the present disclosure that follow the general principles of the present disclosure and include common knowledge or customary technical means in the art that are not disclosed in the present disclosure. The specification and embodiments are to be considered merely as exemplary, and the true scope and spirit of the present disclosure are indicated by the claims.
[0109] It should be understood that the present disclosure is not limited to the exact structures that have been described above and shown in the drawings, and that various modifications and changes may be made without departing from the scope thereof. The scope of the present disclosure is limited only by the appended claims.
Claims
1. A method for preparing an insulating wear-resistant composite coating, characterized in that: The insulating wear-resistant composite coating comprises a metal-ceramic transition layer, a single ceramic layer and a multiphase ceramic surface layer; the metal-ceramic transition layer comprises a metal phase and a ceramic phase, the metal phase is a combination of one or more of nickel, aluminum, cobalt, chromium and yttrium, and the ceramic phase is a combination of one or more of aluminum oxide, yttrium oxide, zirconium oxide, titanium oxide and chromium oxide; the single ceramic layer is aluminum oxide; the multiphase ceramic surface layer comprises a main phase and a doped phase, the main phase is aluminum oxide, and the doped phase is a combination of one or more of yttrium oxide, zirconium oxide, titanium oxide and chromium oxide; wherein the method for preparing the insulating wear-resistant composite coating comprises: Mechanically mixing metal powder corresponding to the metal and ceramic powder corresponding to the ceramic, and obtaining metal-ceramic transition layer powder after drying; Mechanically mixing the alumina powder and the corresponding doped powder, and drying them to obtain the composite ceramic surface layer powder; Using the metal ceramic transition layer powder and plasma spraying to prepare the metal ceramic transition layer on the surface of the substrate; Using aluminum oxide powder and plasma spraying to prepare the single ceramic layer on the metal ceramic transition layer; Using the composite ceramic surface layer powder and plasma spraying to prepare the composite ceramic surface layer on the single ceramic layer; Among them, the thickness of the metal ceramic transition layer is 30μm to 100μm, and the porosity is less than or equal to 5%; the thickness of the single ceramic layer is 100μm to 300μm, and the porosity is less than or equal to 5%; the thickness of the multiphase ceramic surface layer is 100μm to 400μm, and the porosity is less than or equal to 3%.
2. The method for preparing the insulating wear-resistant composite coating according to claim 1, characterized in that: The mass percentage of the ceramic phase in the metal-ceramic transition layer is 5% to 50%.
3. The method for preparing the insulating wear-resistant composite coating according to claim 1, characterized in that: The mass percentage of the doped phase in the composite ceramic surface layer is 1% to 30%.
4. The method for preparing an insulating wear-resistant composite coating according to any one of claims 1 to 3, characterized in that: The DC breakdown voltage of the insulating wear-resistant composite coating is greater than or equal to 4kV, the bonding strength is greater than or equal to 25MPa, and the hardness is 1000HV 0.3 Up to 1400HV 0.3 The average friction coefficient is 0.5 to 0.8, and the wear rate is 1.5×10 -6 mm·N -1 ·m -1 Up to 3.0×10 -6 mm·N -1 ·m -1 .
5. The method for preparing the insulating wear-resistant composite coating according to claim 1, characterized in that: The method for preparing the insulating wear-resistant composite coating further comprises: Before preparing the metal-ceramic transition layer, the substrate is cleaned and dried; The cleaned and dried substrate is roughened using a sandblasting machine.
6. The method for preparing the insulating wear-resistant composite coating according to claim 5, characterized in that: The process parameters for roughening the substrate using the sandblasting machine include: a sandblasting pressure of 0.2 MPa to 0.6 MPa, a distance between the sandblasting gun and the substrate of 5 cm to 20 cm, and a sandblasting angle of 60° to 90°.
7. The method for preparing the insulating wear-resistant composite coating according to claim 1, characterized in that: The process parameters for preparing the metal ceramic transition layer include: spraying power of 40 kW to 80 kW, main gas flow of 60 L / min to 200 L / min, powder feeding rate of 10 g / min to 30 g / min, and spraying distance of 8 cm to 15 cm.
8. The method for preparing the insulating wear-resistant composite coating according to claim 1, characterized in that: The process parameters for preparing the single ceramic layer and / or the composite ceramic surface layer include: spraying power of 40 kW to 100 kW, main gas flow of 60 L / min to 200 L / min, powder feeding rate of 10 g / min to 30 g / min, and spraying distance of 8 cm to 15 cm.
Citation Information
Patent Citations
High-temperature-resistant composite ceramic insulating coating and preparation method thereof
CN112725720A
Insulating coating with composite structure, preparation method of insulating coating and insulating bearing
CN116770300A